Meningkatkan Literasi Tentang Koperasi Syariah Bersama Pimpinan Daerah Aisyiyah Kota Gresik Jawa Timur - Amir Mukadar; Marini Marini; Meilaty Finthariasari Meilaty Finthariasari (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2024)
As a pioneer of the Indonesian women's movement from time to time, the figures of 'Aisyiyah since the beginning of the movement have pioneered their work with a strong spirit of religious belief, a sincere soul, extensive knowledge and intelligence, a humble attitude, tenacity, experience, sincerity, and tireless service in the treasure trove of struggle for Islamic women. The role of 'Aisyiyah is a struggle to jihad in advancing all aspects of life through strengthening spirituality, morals, education, health, economy, social welfare, and other efforts at the community level (congregation community) spread throughout the country. Related to the strong determination and desire of the Aisyiyah Regional Leadership of Gresik City, East Java, and all its members to establish a Cooperative that operates according to the sharia system, we, the Community Service Team of the Faculty of Economics and Business, Muhammadiyah University of Bengkulu, assisted the Aisyiyah Regional Leadership of Gresik City, East Java, in providing training and outreach in the form of Community Service with the theme of increasing Literacy about Sharia Cooperatives in the Aisyiyah Regional Leadership of Gresik City, East Java. Several problems in realizing this desire are the lack of understanding of the teachers at the school about the concept and operation of Sharia Cooperatives and not knowing how to establish a Sharia Cooperative